SYNCHRONIZATION OF OVULATION USING CIDR FOR OVARIAN CYSTS IN CATTLE - HONPARKHE, M; GHUMAN, S P S; SINGH, JAGIR (The Indian Journal of Animal Reproduction, 2011)
The objective of this study was to document ovarian and endocrine responses associated with the treatment of ovarian cysts in dairy cattle, using controlled internal drug release (CIDR) regimens. Eight cattle of group-A were administered GnRH analogue (20μg Buserelin) on day 0, PGF2a (500μg Cloprostenol) on day 7 and 2nd GnRH (20μg Buserelin) on day 9. In addition, CIDR (1 .38g progesterone) was inserted on day 0 till day 7. Eight cows of group-B received PGF 2« (500μg Cloprostenol) on day 0, concurrent with the intravaginal placement of CIDR for 15 days followed by GnRH analogue (20μg Buserelin) on day 17. Cattle were inseminated (Al) at 72 hrs after CIDR removal. In group-A, following day 0 treatment, complete luteinization of cystic structure as well as of large follicle occurred in all cattle (p<0.05). In response to day 7 PGF 20, all the cattle (p<0.05) exhibited a decrease (p<0.05) in plasma progesterone as well as regression (p<0.05) of ovarian cyst/ luteinized follicle on day 10. In group-8 , day 0 treatment, resulted in considerable decrease (p<0.05) in the diameter of cystic structure and the cyst was no longer detectable by day 15. In both groups, all the cattle (p<0.05) exhibited synchronous ovulation between 72- 96 hrs after CIDR removal (or 24-48 h after GnRH injection). Moreover, luteal profile on day 6 po AI as well as conception rate (62.5%) was similar in both the groups. These data suggested that both the Cl DR-based timed Al protocols were equally successful for the treatment of ovarian cyst and recruitment of a follicle for synchronous ovulation in dairy cattle with ovarian cysts.